Land reform: breaking up is hard to do - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The government of South Africa recently swung into action a long-standing set of land reform measures, fearful, some say, of being confronted with similar problems to those in neighbouring Zimbabwe. The measures provide for the redistribution of...